CONSUMER PRIVACY CONCERN, TRUST, AND INTIMACY AS DRIVERS OF E-LOYALTY: THE MODERATING ROLE OF NEED FOR RELATEDNESS IN SHOPEE USERS - Arinto, Boby; Kusuma Among Praja, Arief; Arief Wahyudi, Triyono; Angga Negoro, Dimas (ULTIMA Management, 2025)
Abstract- Indonesia’s e-commerce adoption continues to grow as consumers increasingly rely on digital platforms for transactional convenience. Shopee remains the most dominant marketplace in Indonesia, leading both market share and platform engagement. This study investigates how consumer privacy concern, online trust, and brand intimacy shape e-loyalty in the Shopee ecosystem. Additionally, the moderating role of need for relatedness is examined to understand individual differences in forming relational bonds with the platform. Using a survey of 225 Shopee users in Greater Jakarta and applying PLS-SEM, the findings demonstrate: (1) privacy concern negatively affects trust and intimacy, (2) trust positively influences intimacy and e-loyalty, (3) intimacy strongly predicts e-loyalty, and (4) need for relatedness strengthens the trust–intimacy relationship. The study offers theoretical advancement by integrating privacy, trust, and relational bonding theories in a marketplace context and highlights practical strategies for fostering customer loyalty through relational experiences.Keywords: Privacy Concern; Online Trust; Brand Intimacy; E-Loyalty; Need for Relatedness; Shopee.